Harmony and a full life, notions that guide the Tseltal way of life - Antonio Miguel, Nancy Beatriz; Parra Vázquez, Manuel Roberto; Ramos Maza, María Teresa; Herrera Hernández, Obeimar Balente (Agricultura, Sociedad y Desarrollo, 2021)
This article analyzes the way in which the live categories jun pajal oÂ´tanil (a single heart) and lequil cuxlejal (full live) guide the process of cultural change among the tseltal families linked to the Jesuit Mision in Bachajón. The experience of the â€œsustainable tzeltal homeâ€ built by a group of peasant women from Pinabetal, municipality of Chilón, Chiapas, was analyzed as a study case. Documental information was reviewed and interviews, focal groups, and workshops were performed. The robustness of the system of the community charge system and the enhancement of local capacities were the pillars to build autonomous processes of change, which allowed improving the living and working conditions of the tseltal families. It is concluded that with a foundation in the cultural roots of the tseltal people, peasant families adopt innovations through a process of cultural control.